Intelegensi dalam Perspektif Psikologi Pendidikan - Fitri Wahyuni Sabulat; Satinah Satinah; Taufik Rahman (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Intelligence is an individual's ability to comprehend, connect, and solve a variety of problems. This study reviews the concept of intelligence from various perspectives, including definitions, classifications of intelligence, and the factors that influence it. This study also discusses multiple intelligences such as intellectual quotient (IQ), emotional quotient (EQ), and spiritual quotient (SQ), as well as various other forms of intelligence based on Howard Gardner's theory. Heredity and environment are presented as the main determinants of individual intelligence development. This study aims to understand the complexity of human intelligence and how intelligence can be applied in learning, especially in Islamic religious education.